2000
DOI: 10.3109/08923970009016412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of San-Ao-Tang on Immediate and Late Airway Response and Leukocyte Infiltration in Asthmatic Guinea Pigs

Abstract: San-Ao-Tang (SAT), a traditional Chinese medicines, has been used to treat patients with the bronchial asthma for several centuries. However, the therapeutic mechanisms of this Chinese medicine are still far from clear. To understand the mechanism of antiasthmatic property of SAT, a guinea pig model of allergic asthma was used to investigate the effects of SAT on Dermatophagoides pteronyssinus-induced immediate and late asthmatic responses and airway inflammation. Our results showed that administration of SAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Different sensitization processes may induce different severities of antigen reactions. Booster sensitization by an aerosolized antigen has been widely used in recent years, as this antigen delivery route is similar to the natural physiological way, and this method can elicit responses including elevated levels of allergen-specific IgE, eosinophilic airway inflammation, and AHR [8,14-16]. On the other hand, delivery of medication directly to the airways has a quicker action than the oral route, as the drug can act immediately upon the target area.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Different sensitization processes may induce different severities of antigen reactions. Booster sensitization by an aerosolized antigen has been widely used in recent years, as this antigen delivery route is similar to the natural physiological way, and this method can elicit responses including elevated levels of allergen-specific IgE, eosinophilic airway inflammation, and AHR [8,14-16]. On the other hand, delivery of medication directly to the airways has a quicker action than the oral route, as the drug can act immediately upon the target area.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the Chinese herbs used for the treatment of bronchial asthma are either administered orally or through a gastric tube for research purposes. For example, several studies have demonstrated the anti-asthmatic effects of traditional Chinese medicine formulas such as XQLT by administering the medicine via the gastric route to guinea pigs [14-16], and simplified herbal medicine treatment also reduced several asthma features in a mouse model [27,28]. Currently, many of the western medicines used for the treatment of asthma are inhaled.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations